2012
DOI: 10.21273/jashs.137.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Plant Growth Regulators to Container-grown Citrus Trees Affect the Biology and Behavior of the Asian Citrus Psyllid

Abstract: Asian citrus psyllid [ACP (Diaphorina citri)] is an important pest of citrus (Citrus sp.) in many citrus-growing regions of the world because of its status as the vector of huanglongbing disease [HLB (citrus greening)]. There are currently no HLB-resistant citrus genotypes and no proven treatments for the disease; thus, vector control through the use of frequent prophylactic pesticide applications is key to managing the spread of this disease. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 47 publications
2
12
0
Order By: Relevance
“…Exogenous application of calcium to developing shoots has been associated with reduced D . citri population and infestation levels [41,42] presumably due to enhanced cell wall thickening and lignification which are unsuitable for egg-laying or feeding. Taken together, D .…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous application of calcium to developing shoots has been associated with reduced D . citri population and infestation levels [41,42] presumably due to enhanced cell wall thickening and lignification which are unsuitable for egg-laying or feeding. Taken together, D .…”
Section: Discussionmentioning
confidence: 99%
“…(Ericaceae) because of reduced nutrient availability. Tsagkarakis et al (2012) found that Diaphorina citri Kuwayama (Hemiptera: Liviidae) adults reared on Citrus volkameriana (Rutaceae) trees treated with prohexadione calcium and mefluidide showed significant reductions in both fecundity and survivorship. However, no effect of plant growth regulator use on the suitability of creeping bentgrass against black cutworms, Agrotis ipsilon Hufnagel (Lepidoptera: Noctuidae), and sod webworms (Lepidoptera: Pyralidae) was evident (Rogers et al 2001).…”
Section: Effect Of Plant Growth Regulators On Blissus Insularis (Hemimentioning
confidence: 99%
“…The life cycle of the ACP is closely related to the presence of new flush shoots in plants. In the tropics, the continuous production of new flush shoots allows ACP populations to remain relatively high at various times of the year, rendering control with systemic or contact insecticides difficult because the new growth cannot be continuously protected by pesticides (Pluke et al, 2008;Tsagkarakis et al, 2012). The strategy of applications of synthetic elicitors can be considered as an effective option in arthropod pest management programs because synthetic elicitors are small molecules that can induce immune responses in plants and produce a positive effect in the management of ACP populations (Pawlowski et al, 2016).…”
mentioning
confidence: 99%
“…Elicitors are compounds that stimulate any type of defense in the plant and favor the synthesis of secondary metabolites under conditions of both abiotic and biotic stress and can be applied through foliar sprays. Within these compounds, carbohydrates, lipids, (glyco)peptides, (glyco)proteins, vitamins, and phytohormones can be found (Angelova et al, 2006;Boubakri et al, 2016;Smith et al, 2009;Thakur and Sohal, 2013;Tsagkarakis et al, 2012). Among the compounds studied to activate defense mechanisms in plants against the attack of biotic agents (macro-and microorganisms) are SA, phytohormones, chitosan, and thiamine (vitamin B1) (Ahn et al, 2005;El Hadrami et al, 2010;Thakur and Sohal, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation